Peut-on considerer qu’un nouveau droit du maintien dans l’emploi est en cours d’élaboration ? - Hervé Gosselin (Perspectives Interdisciplinaires sur le Travail et la Santé)
The employer’s obligations regarding the reclassification of a salaried employee who cannot remain at his job, is subject to two different legal rules, depending on whether the employee is declared “able,” subject to adaptation of his workstation, or "disabled" by the occupational physician. This distinction is not relevant ; it is a source of legal insecurity and it orients the judge’s control towards the regularity of the contestation of work disability at the expense of a verification that the employer has done everything necessary to adapt the position or to reclassify the salaried employee. However, the growing use of the concept of "result safety obligation" by the Chambre sociale de la Cour de cassation, and the influence of the community antidiscrimination law could be at the origin of a reorientation of this control towards the employer’s obligation to comply with reclassification. In this field, the use of the employees’ competences by the representative institutions could only encourage the judge to exert this delicate control, which must reconcile the employers’ respect for their very strong obligations and their necessary consideration of management constraints.